Spectrophotometric estimation of pioglitazone hydrochloride in tablet dosage form - Basniwal, Pawan K; Srivastava, Prabhat K; Jain, Deepti (Asian Journal of Pharmaceutics (AJP), 2014)
Two simple, rapid, and precise methods - linear regression equation (LRE) and standard absorptivity - were developed and validated for the estimation of pioglitazone hydrochloride in tablet dosage form. The maximum absorbance (Î»max) of pioglitazone hydrochloride was found to be 269.8 nm in methanol:water:hydrochloric acid (250:250:1). Beer-Lambert law was obeyed in the concentration range of 10-50 Î¼g/ml, and the standard absorptivity was found to be 253.97 dl/g/cm. Both the methods were validated for linearity, accuracy, precision (days, analysts, and instrument variation), and robustness (solvent composition). The numerical values for all parameters lie within the acceptable limits. Pioglitazone hydrochloride was estimated in the range of 99.58-99.97% by LRE method and 100.25-100.75% by standard absorptivity method. At 99% confidence limit, the F-test value for the methods was found to be 1.8767